Chitosan Treatment Promotes Wound Healing of Apple by Eliciting Phenylpropanoid Pathway and Enzymatic Browning of Wounds - Ackah, Sabina; Xue, Sulin; Osei, Richard; Kweku-Amagloh, Francis; Zong, Yuanyuan; Prusky, Dov; Bi, Yang (Frontiers in Microbiology, 2022)
Chitosan is an elicitor that induces resistance in fruits against postharvest diseases but there is little knowledge about the wound healing ability of chitosan on apple fruits. Our study aimed at revealing the effect of chitosan on the phenylpropanoid pathway, by determining some enzyme activities, products metabolites, polyphenol oxidase activity, color (L*, b*, a*), weight loss, and disease index during healing. Apple (cv. Fuji) fruits wounded artificially were treated with 2.5% chitosan and healed at 21−25 °C, RH= 81–85% for 7d and non-wounded fruits (coated and non-coated) were used as control. The result shows that chitosan treatment significantly decreased weight loss of wounded fruits and disease index of Penicillium expansum inoculated fruits. The activities of phenylalanine ammonia-lyase, cinnamic acid 4-hydroxylase, 4-coumaryl coenzyme A ligase, cinnamoyl-CoA reductase, and cinnamyl-alcohol dehydrogenase were elicited throughout the healing period by chitosan, which increased the biosynthesis of cinnamic acid, caffeic acid, ferulic acid, sinapic acid, p-coumaric acid, p-coumaryl alcohol, coniferyl alcohol, and sinapyl alcohol. Also, total phenol, flavonoid, and lignin contents were significantly increased at the fruits wounds. In addition, chitosan’s ability to enhance polyphenol oxidase activity stimulated enzymatic browning of wounds. Although wounding increased phenylpropanoid enzymes activities prior to healing, chitosan caused higher enzyme activities for a significant healing effect compared to the control. These findings imply that chitosan accelerates apple wound healing by activating the phenylpropanoid pathway and stimulating enzymatic browning of wounds.